Knowledge and Behavior Regarding Antibiotic Stewardship in Health Workers at Sultan Syarif Mohammad Alkadrie Hospital, Indonesia - Restika, Risma A.; Mardhia, Mardhia; Mahyarudin, Mahyarudin; Liana, Delima F.; IH, Hariyanto (Universitas Padjadjaran, Indonesia, 2024)
Antimicrobial resistance is a global public health concern. The World Health Organization reports that antimicrobial resistance constitutes a serious threat to public health worldwide. One of the risk factors in the development of antimicrobial resistance cases is the irrational use of antibiotics. Knowledge and behavior of health worker about antibiotic stewardship play a role in preventing antibiotic resistance cases. This study aimed to demonstrate knowledge and behavior regarding antibiotic stewardship in health workers at Sultan Syarif Mohamad Alkadrie Hospital, Pontianak. This was a cross-sectional descriptive study using consecutive sampling with total of 39 respondents. Data were collected through questionnaires with total of 45 questions. Knowledge and behavior of respondents were categorized as good, moderate, and low. The data was analyzed using the spearman rank correlation coefficient. The results showed that most health workers had good knowledge 97.44% (38/39) and good behavior 87.18% (34/39) related to antibiotic stewardship with a spearman p-value >0.05. Antibiotic stewardship is important for health workers to prevent an increase in antibiotic resistance cases and their impact on public health worldwide. As we know, increasing antibiotic resistance is a globally major problem as health system depends on effective antibiotics to treat bacterial infections.